BOARD GENDER, EDUCATION, AND SIZE: CAN THEY SUPPRESS TAX AVOIDANCE? - Sugeng, Laurencia Nathania Marcella; Radianto, Wirawan Endro Dwi (Jurnal Aplikasi Akuntansi, 2025)
The characteristics of the Board of Directors are crucial in shaping a company's strategic decisions, including tax-related policies. This research analyzes the effect of board size, directors' educational background, and gender diversity on tax avoidance. The energy sector is important because of its strategic contribution to the economy, and to explore how internal governance, particularly the board of directors, may influence tax avoidance practices within this industry. The study focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023, with the sample selected through purposive sampling, and the data were analyzed using a panel data regression approach to examine the relationships among the variables. The findings indicate that the gender diversity, educational background of directors, and board size do not significantly affect tax avoidance.